1991
DOI: 10.1210/jcem-72-2-432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects on Insulin Sensitivity of High Carbohydrate and High Fat Diets in Normal Subjects*

Abstract: To examine whether achievable dietary changes influence insulin sensitivity, we performed euglycemic hyperinsulinemic glucose clamps in eight normal subjects who were prescribed high carbohydrate and high fat diets. The high carbohydrate diet was more than 50% (of energy intake) carbohydrate and less than 30% fat; the high fat diet was more than 45% fat (predominantly saturated) and less than 40% carbohydrate. The diets were consumed over consecutive 3-week periods in random sequence. The mean whole body gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 39 publications
5
52
1
Order By: Relevance
“…This finding is consistent with the well-reported hypertriglyceridemic effects of carbohydrate rich diets. 22,23 The plasma ß-hydroxy-butyrate concentration was increased in the two groups that consumed the fat-rich diet, which is consistent with the reported ketogenic effect of fat-rich diets. 24 Furthermore the finding of a significantly higher muscle glycogen concentration after the consumption of the carbohydraterich diet and not in either of the groups that consumed the fat-rich diet is consistent with a higher carbohydrate intake.…”
Section: Discussionsupporting
confidence: 79%
“…This finding is consistent with the well-reported hypertriglyceridemic effects of carbohydrate rich diets. 22,23 The plasma ß-hydroxy-butyrate concentration was increased in the two groups that consumed the fat-rich diet, which is consistent with the reported ketogenic effect of fat-rich diets. 24 Furthermore the finding of a significantly higher muscle glycogen concentration after the consumption of the carbohydraterich diet and not in either of the groups that consumed the fat-rich diet is consistent with a higher carbohydrate intake.…”
Section: Discussionsupporting
confidence: 79%
“…After adjusting for these variables, there was no association between GHb and adult height (Ohlson et al, 1987), in contrast to some reports which associated type 2 diabetes with shorter stature (Brown et al, 1991). The inverse association between GHb and educational attainment was consistent with the well described inverse association between type 2 diabetes and socio-economic status (Rewers & Hamman, 1995).…”
Section: Discussionmentioning
confidence: 59%
“…Evidence that high-carbohydrate, high®bre diets contribute to improved insulin sensitivity in nondiabetic subjects is con¯icting (Fugakawa et al, 1990;Borkman et al, 1991) but Salmeron et al (1997) suggested that diets with a high glycaemic load and low cereal ®bre content contributed to the risk of type 2 diabetes. In an extensive review, Daly et al (1997) concluded that there was insuf®cient evidence from human studies to draw ®rm conclusions concerning the relation between dietary carbohydrate and insulin sensitivity.…”
Section: Diet and Glycated Haemoglobin MC Gulliford And Oc Ukoumunnementioning
confidence: 99%
“…However, this evidence is not supported by prospective studies where dietary habits have been related to the development of NIDDM (188,189). The effects of a high carbohydrate diet on glucose tolerance have been equivocal (190,191). Hughes et al (192) compared the effects of a high carbohydrate (60% carbohydrate and 20% fat)/high fibre (25 g dietary fibre/1000 kcal th ) diet with, and without, three months of high-intensity endurance exercise (75% maximal heart rate reserve, 50 minutes/day, four days/week) in older glucoseintolerant men and women.…”
Section: Exercise In the Treatment Of Glucose Intolerance And Niddmmentioning
confidence: 97%